Spinel lithium manganate cathode material and preparation method thereof

CN122291500BActive Publication Date: 2026-10-13XIANGTAN ELECTROCHEMICAL SCI CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202610751430.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-10-13
Estimated Expiration
2046-05-28

AI Technical Summary

Technical Problem

然而,其商业化应受到2大固有缺陷的制约:(1)高温(55℃以上)循环性能差,充放电循环过程中比容量衰减严重

Benefits of technology

本发明采用掺杂尖晶石锰酸锂为内核,类单晶锰酸锂为包覆层的核壳结构。内核中掺杂元素呈由内向外递减的梯度分布,内部高掺杂浓度有效抑制了Jahn-Teller效应和锰溶出,稳定体相结构;表面低掺杂浓度使表层区域接近本征锰酸锂,保持快速锂离子脱嵌活性,使材料具备优异的高温循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122291500B_ABST
    Figure CN122291500B_ABST
Patent Text Reader

Abstract

The application provides a spinel lithium manganate positive electrode material and a preparation method thereof. a Mn 2‑x M x O4, wherein M is a doping element, 0.95<=a<=1.10, 0 The material is obtained by co-precipitation to obtain a doping precursor, mixing with a lithium source for sintering to obtain the core, mechanically mixing the core with manganese hydroxide, adding a lithium source for mixing and sintering. The material realizes high-temperature cycle stability, high tap density, high compaction density and excellent rate performance through the synergistic design of "doped core + homologous electrochemically active coating".
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and in particular to a spinel lithium manganese oxide cathode material and its preparation method. Background Technology

[0002] Spinel lithium manganese oxide cathode material is considered one of the most ideal cathode materials for power lithium-ion batteries. It has attracted widespread attention in the power and energy storage fields due to its low cost, environmental friendliness, stable low-temperature performance, excellent rate performance, and high voltage platform. However, its commercialization is constrained by two inherent defects: (1) poor high-temperature (above 55°C) cycle performance, with severe capacity decay during charge-discharge cycles. The main reason is that a small amount of water in the electrolyte reacts with LiPF6 in the electrolyte to generate HF, leading to the degradation of Mn... 3+ A disproportionation reaction occurs to generate Mn. 4+ and Mn 2+ Mn 2+ Dissolution occurs, with a faster rate at high temperatures, damaging the spinel structure of lithium manganese oxide and resulting in poor high-temperature cycling performance. Simultaneously, when the average valence state of Mn is below +3.5, the Jahn-Taylor effect is induced. (1) The Teller effect causes crystal structure distortion, transforming from a cubic system to a tetragonal system, resulting in lattice distortion, which enhances the polarization effect of the electrode and causes specific capacity decay. (2) The primary particles of the material are easy to grow into an octahedral morphology, with many internal pores between the particles, making it difficult to arrange them tightly under gravity or external force. This results in a high porosity during compaction and compaction, and a low compaction and compaction density, which directly affects the energy density of the battery and the processing performance of the electrode.

[0003] To address these challenges, existing technologies primarily focus on bulk doping and surface coating. Bulk doping enhances the stability of the spinel structure during cycling by introducing dopant elements, thereby suppressing Jahn emissions. The Teller effect mitigates specific capacity decay. However, doping elements can introduce ion diffusion barriers, increasing lithium-ion insertion / extraction resistance and negatively impacting the material's rate performance. Surface modification, by constructing a protective layer on the surface of lithium manganese oxide particles, reduces direct contact between lithium manganese oxide and the electrolyte, thereby decreasing Mn dissolution in the electrolyte and improving high-temperature cycling performance. However, existing coating technologies still have the following shortcomings: This document, published in China (CN101807682A) on August 18, 2010, discloses a power-type spinel lithium manganese oxide cathode material. It employs Nb and Al doping modification and is coated with composite oxides such as lithium nickel, lithium cobalt, lithium magnesium, or lithium boron. While this approach can improve cycle performance to some extent, the coating materials used are all electrochemically inert and do not participate in the charge-discharge reaction, thus hindering lithium-ion transport and impairing the material's rate performance. Furthermore, this type of inert coating layer does not significantly improve tap density and compaction density.

[0004] The first document, published in China (CN107086298A, August 22, 2017), discloses a core-shell heterogeneous lithium-ion battery composite cathode material composed of layered lithium-rich manganese-based and spinel-type lithium manganese oxide, and its preparation method. The layered lithium-rich manganese-based shell is prepared using a PVP-assisted combustion method or a wet chemical method. The second document, also published in China (CN119833606A, April 15, 2025), discloses a manganese-based composite cathode material, its preparation method, and its applications. The lithium-rich manganese-based shell is grown in situ using a secondary co-precipitation method. Both documents propose a core-shell structure with spinel-type lithium manganese oxide as the core and layered lithium-rich manganese-based material as the shell. However, they have the following shortcomings: although the shell material has electrochemical activity, its crystal structure is layered, which differs significantly from the spinel structure of the core. This heterostructure leads to lattice mismatch, increases interfacial impedance, and affects the cross-interface transport of lithium ions; at the same time, layered lithium-rich manganese-based materials contain expensive elements such as Ni and Co, which increases the material cost.

[0005] The document, published in China (CN105680025A) on June 15, 2016, discloses a lithium-ion battery cathode material, its preparation method, and a lithium-ion battery. The material is coated with Li... a B b O c Spinel lithium nickel manganese oxide cathode materials with LiMnBO3, although the LiMnBO3 in the coating layer is electrochemically active, also contain inert Li. a B b O c The composition is described, and the material system in this literature is nickel-containing lithium nickel manganese oxide. Furthermore, the simple solid-state mixing sintering process makes it difficult to form a continuous, dense coating layer chemically bonded to the core.

[0006] This document, published in China (CN118676324A) on September 20, 2024, discloses a composite lithium manganese oxide, its preparation method, cathode, battery, and power supply device. It employs a bilayer heterogeneous shell structure consisting of a first coating layer of doped lithium manganese oxide and a second coating layer of doped element compounds, including tetrahydropalmatine (Te) and transition metal elements. The material utilizes the high valence state of Te to form strong covalent bonds with surrounding oxygen atoms, reducing surface oxygen activity. Simultaneously, the physical barrier effect of the second coating layer suppresses electrolyte side reactions, thereby improving high-temperature storage and cycling performance. However, this material still has the following shortcomings: First, it relies on the synergistic effect of Te and specific transition metals (Nb, Mo, Ta, W, Sb, etc.), but Te is relatively scarce and expensive, which is not conducive to large-scale industrial applications; Second, the bilayer heterostructure leads to an increase in interfaces and the risk of lattice mismatch, and the preparation process is complex, requiring precise control of the sintering temperature and dopant distribution in both stages, which increases the difficulty of production and energy consumption; Third, the second coating layer of this material is an electrochemically inert material that does not participate in electrochemical reactions. It not only fails to provide capacity but also introduces additional interfacial impedance, hindering lithium-ion cross-interface transport.

[0007] In summary, existing technologies have improved the stability, tap density, and compaction density of materials to some extent, but they often come at the cost of one thing: bulk doping can stabilize the structure but may introduce ion diffusion barriers and sacrifice rate performance; inert material coating can suppress side reactions but will hinder ion transport and does not contribute to capacity; and heterostructure coating faces problems such as lattice mismatch and increased interfacial impedance. Summary of the Invention

[0008] This application is made in view of the above-mentioned problems, and its purpose is to provide a spinel lithium manganese oxide cathode material and its preparation method, which can simultaneously stabilize the bulk structure of spinel lithium manganese oxide, improve the tap density and compaction density of the material, while not affecting the ion diffusion kinetics and electronic conduction ability, and the coating layer itself has electrochemical activity.

[0009] Specifically, the first aspect of this application provides a spinel lithium manganese oxide cathode material, comprising a doped spinel lithium manganese oxide core and a near-monocrystalline lithium manganese oxide coating layer covering the doped spinel lithium manganese oxide core, wherein the chemical formula of the doped spinel lithium manganese oxide core is Li. a Mn 2-x M x O4, where 0.95≤a≤1.10, 0<x≤0.5, and M is a doping element selected from one or more of B, Mg, Al, Ti, Ga, Sr, Zr, Nb, Ba, La, Ce, and Ta.

[0010] Optionally, the doped spinel lithium manganese oxide core is a gradient-doped spinel lithium manganese oxide, with the doping concentration decreasing from the inside to the outside.

[0011] Optionally, the mass of the quasi-monocrystalline lithium manganese oxide coating layer accounts for 0.2% to 5.0% of the total mass of the spinel lithium manganese oxide cathode material.

[0012] Optionally, the doping element is Al and / or Mg.

[0013] Optionally, the primary particles of the doped spinel lithium manganese oxide core have a polyhedral morphology.

[0014] Optionally, the average particle size D50 of the primary particles of the doped spinel lithium manganese oxide core is 50 nm to 500 nm.

[0015] Optionally, the primary particles of the doped spinel lithium manganese oxide core have a pure-phase spinel structure with a space group of Fd-3m.

[0016] Optionally, the primary particles of the doped spinel lithium manganese oxide core have an octahedral or truncated octahedral morphology.

[0017] Optionally, the average particle size D50 of the primary particles of the doped spinel lithium manganese oxide core is 150 nm to 300 nm.

[0018] Optionally, in the XRD pattern of the doped spinel lithium manganese oxide core, the ratio of the diffraction peak intensity of the (111) crystal plane to the diffraction peak intensity of the (400) crystal plane is in the range of 2.4≤I(111) / I(400)≤2.6.

[0019] A second aspect of this application provides a method for preparing a spinel lithium manganese oxide cathode material, comprising the following steps: S1: Containing Mn 2+ A co-precipitation reaction is carried out by adding a soluble salt solution of the doped cation, a precipitant solution, and a complexing agent in a parallel flow to obtain the doped precursor; S2: The doped precursor and lithium source are uniformly mixed at a molar ratio (Mn+M):Li of 1:0.48~0.58, and sintered in an oxygen-containing atmosphere to obtain a doped spinel lithium manganese oxide core. S3: The spinel lithium manganese oxide core is mechanically mixed with manganese hydroxide to obtain manganese hydroxide-coated lithium manganese oxide. The manganese hydroxide-coated lithium manganese oxide is mixed with a lithium source, wherein the molar ratio of manganese atoms in the manganese hydroxide to lithium atoms in the lithium source (Mn:Li) is 2:1. The mixture is then sintered at high temperature in an oxygen-containing atmosphere to obtain the spinel lithium manganese oxide cathode material.

[0020] Optionally, in step S1, a soluble salt solution is prepared according to the chemical formula of the doped spinel lithium manganese oxide core, in which the molar ratio of Mn:M is (2-x):x, wherein 0 < x ≤ 0.5.

[0021] Optionally, the precipitant in step S1 is selected from one or more of sodium hydroxide and potassium hydroxide.

[0022] Optionally, the complexing agent in step S1 is selected from one or more of ammonia, ammonium carbonate, and ammonium bicarbonate.

[0023] Optionally, in step S1, the flow rate of the soluble salt solution containing the doped cation is reduced in stages, wherein the flow rate is 20 mL / min to 5 mL / min.

[0024] Optionally, the temperature of the co-precipitation reaction in step S1 is 40℃~80℃.

[0025] Optionally, the pH value of the co-precipitation reaction in step S1 is 9.0 to 13.0.

[0026] Optionally, in step S1, oxygen is introduced for pre-oxidation during the co-precipitation reaction, with an oxygen flow rate of 1 m³ / s. 3 / h~10m 3 / h.

[0027] Optionally, after the co-precipitation reaction in step S1 is completed, the co-precipitated slurry is further filtered, washed, and dried.

[0028] Optionally, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium nitrate, lithium sulfate, lithium acetate, lithium phosphate, lithium fluoride, lithium chloride, and lithium citrate.

[0029] Optionally, the oxygen-containing atmosphere is air or oxygen, and the gas flow rate is 1 m / s. 3 / h~10m 3 / h.

[0030] Optionally, the sintering process further includes crushing and sieving, with a sieving mesh size of 200 to 500 mesh.

[0031] Optionally, the sintering temperature in step S2 is 700℃~900℃.

[0032] Optionally, the sintering time in step S2 is 8h to 24h.

[0033] Optionally, the manganese hydroxide in step S3 is battery-grade micron-sized manganese hydroxide.

[0034] Optionally, step S3 may further include premixing and screening before mechanical mixing, with a screening mesh size of 200 to 500 mesh.

[0035] Optionally, the mechanical mixing in step S3 is a combination of low-speed mixing and high-speed mixing performed sequentially, with the low-speed mixing speed being 500 rpm to 2000 rpm and the high-speed mixing speed being 3000 rpm to 6000 rpm.

[0036] Optionally, the mechanical mixing time in step S3 is 1 min to 10 min.

[0037] Optionally, the sintering temperature in step S3 is 700℃~900℃.

[0038] Optionally, the sintering time in step S3 is 8h to 24h.

[0039] Compared with the prior art, the present invention has the following beneficial effects: This invention employs a core-shell structure with doped spinel lithium manganese oxide as the core and quasi-monocrystalline lithium manganese oxide as the coating layer. The doping elements in the core exhibit a gradient distribution decreasing from the inside out. The high doping concentration inside effectively suppresses the Jahn-Teller effect and manganese dissolution, stabilizing the bulk structure. The low doping concentration on the surface makes the surface region resemble intrinsic lithium manganese oxide, maintaining rapid lithium-ion insertion / extraction activity and giving the material excellent high-temperature cycling performance.

[0040] The coating layer is a homologous electrochemically active quasi-monocrystalline lithium manganese oxide, which, like the core, has a spinel structure and high lattice matching. Its electrochemical activity ensures that lithium-ion diffusion kinetics and electronic conduction are not affected, overcoming the defect of traditional inert coating layers that hinder ion transport. The coating layer itself participates in the electrochemical reaction and provides capacity. During charging and discharging, it forms a more stable binding phase with the core, slowing down the process of lattice distortion, reducing the dissolution of manganese ions, and improving the structural stability of the material. Its spinel structure provides a three-dimensional lithium-ion diffusion channel. Combined with optimized crystal orientation, it is conducive to the rapid insertion and extraction of lithium ions along specific crystal planes, thus giving the material excellent rate performance.

[0041] The quasi-monocrystalline lithium manganese oxide coating of the present invention forms a dense and continuous shell through mechanical fusion and secondary sintering, which fills the defects on the surface of the spinel lithium manganese oxide core, resulting in a more compact particle packing and thus improving the tap density and compaction density of the spinel lithium manganese oxide cathode material.

[0042] This invention employs a "mechanical fusion + secondary lithium supplementation sintering" preparation method, which enables the coating layer structure to form a dense, continuous, homogeneous, and electrochemically active near-monocrystalline lithium manganese oxide coating layer through direct chemical bonding or close physical contact with the surface of the internal particles. This results in strong interfacial bonding and low interfacial impedance. Furthermore, the preparation method is simple, cost-controllable, and suitable for industrial production.

[0043] In summary, this invention, through the synergistic design of a "doped spinel lithium manganese oxide core" and a "homogeneous electrochemically active single-crystal lithium manganese oxide coating layer," has for the first time achieved a spinel lithium manganese oxide cathode material that simultaneously maintains high-temperature cycling stability, high tap density, high tap density, and excellent rate performance, resulting in significant beneficial effects. Attached Figure Description

[0044] To more clearly illustrate the technical solutions in the embodiments of this drawing or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this drawing. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0045] Figure 1 This is a TEM image of the spinel lithium manganese oxide cathode material prepared in Example 1.

[0046] Figure 2 The images show the XRD patterns of the spinel lithium manganese oxide cathode materials prepared in Examples 1-3 and Comparative Examples 1-3.

[0047] Figure 3 Comparison of XRD diffraction peaks of the (111) crystal plane of the spinel lithium manganese oxide cathode materials prepared in Examples 1-3 and Comparative Examples 1-3. Detailed Implementation

[0048] To make the objectives, technical solutions, and advantages of this application clearer, the following description and illustration are provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application. All other embodiments obtained by those skilled in the art based on the embodiments provided in this application without inventive effort are within the scope of protection of this application.

[0049] Obviously, the following description is merely some examples or embodiments of this application. Those skilled in the art can apply this application to other similar scenarios without any inventive effort. Furthermore, it is understood that although the effort involved in such development may be complex and lengthy, for those skilled in the art related to the content disclosed in this application, any changes to design, manufacturing, or production based on the technical content disclosed in this application are merely conventional technical means and should not be construed as insufficient disclosure of the content of this application.

[0050] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0051] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0052] On one hand, embodiments of this application provide a spinel lithium manganese oxide cathode material, comprising a doped spinel lithium manganese oxide core and a near-monocrystalline lithium manganese oxide coating layer covering the doped spinel lithium manganese oxide core, wherein the chemical formula of the doped spinel lithium manganese oxide core is Li. a Mn 2-x M x O4, where 0.95≤a≤1.10, 0<x≤0.5, and M is a doping element selected from one or more of B, Mg, Al, Ti, Ga, Sr, Zr, Nb, Ba, La, Ce, and Ta.

[0053] This invention employs a core-shell structure with doped spinel lithium manganese oxide as the core and electrochemically active quasi-monocrystalline lithium manganese oxide as the coating layer. This structure features high lattice matching, and the coating layer itself possesses a spinel three-dimensional tunnel structure, allowing lithium ions to pass through freely. The coating layer itself participates in the electrochemical reaction and provides capacity. The coating layer and the core form a more stable bonding phase, which slows down the process of lattice distortion, reduces the dissolution of manganese ions, and improves the structural stability of the material.

[0054] This invention employs one or more doping elements selected from B, Mg, Al, Ti, Ga, Sr, Zr, Nb, Ba, La, Ce, and Ta to dope spinel lithium manganese oxide, and further controls the doping amount to effectively suppress the Jahn-Teller effect of lithium manganese oxide, enhance the stability of the lithium manganese oxide bulk phase, increase the particle size, reduce the specific surface area, and inhibit Mn dissolution.

[0055] The cations of doping elements B, Mg, Al, and Ga are introduced into the Mn sites of spinel lithium manganese oxide crystals through doping, and react with O. 2- It forms stronger MO bonds (M represents B, Mg, Al, Ga) than Mn-O bonds, suppressing the Jahn-Teller effect in spinel lithium manganese oxide.

[0056] The cations of doping elements Ti, Zr, Nb, and Ta (high-valence cations) can be introduced into the Mn sites in spinel lithium manganese oxide crystals, thereby increasing the average valence state of manganese ions and suppressing the Jahn-Teller effect in spinel lithium manganese oxide.

[0057] The cations of doping elements Sr and Ba (with relatively large ionic radii) can partially occupy the Mn sites or grain boundary sites in spinel lithium manganese oxide crystals through doping, acting as pillars and relieving lattice shrinkage / expansion stress.

[0058] The cations (rare earth ions) of doping elements La and Ce can be enriched at the grain boundaries of spinel lithium manganese oxide crystals through doping, which can inhibit excessive grain growth, stabilize the surface lattice, and reduce side reactions with the electrolyte.

[0059] In some embodiments of this application, the doped spinel lithium manganese oxide core is a gradient-doped spinel lithium manganese oxide, with the doping concentration decreasing from the inside to the outside.

[0060] The high doping concentration in the core effectively suppresses the Jahn-Teller effect and manganese dissolution, stabilizing the bulk structure, by distributing doped elements from the inside out. The low doping concentration on the surface makes the surface region close to intrinsic lithium manganese oxide, maintaining rapid lithium-ion insertion / extraction activity, and giving the material excellent high-temperature cycling performance.

[0061] In some embodiments of this application, the mass of the quasi-monocrystalline lithium manganese oxide coating layer accounts for 0.2% to 5.0% of the total mass of the spinel lithium manganese oxide cathode material.

[0062] The positive effects of controlling the quality of the coating layer in single-crystal lithium manganese oxide: When the coating layer quality is below 0.2%, it is difficult to form a complete and continuous shell on the core surface. Instead, it exists as discontinuous, "island-like" particles, failing to form an effective physical barrier. This exposes the core surface to the electrolyte, making it unable to suppress manganese dissolution and interfacial side reactions, resulting in poor high-temperature cycling performance. While a coating layer quality above 5.0% can better protect the core, the average specific capacity of the spinel lithium manganese oxide cathode material will significantly decrease due to the excessively high proportion of low-capacity coating layers, sacrificing the material's energy density. Furthermore, an excessively thick coating layer increases the lithium-ion insertion / extraction distance, introducing more grain boundaries and increasing interfacial impedance. Therefore, the coating layer quality should be controlled to be between 0.2% and 5.0% of the total mass of the spinel lithium manganese oxide cathode material.

[0063] In some embodiments of this application, the doping element is preferably Al and / or Mg.

[0064] Al 3+ With O 2- It has strong bond energy and abundant resources, and can significantly inhibit the Jahn-Teller effect.

[0065] Mg 2+ Ionic radius and Mn 3+ Similar to each other, they are easy to enter the crystal lattice without causing lattice distortion, and at the same time improve structural stability.

[0066] In some embodiments of this application, the primary particles of the doped spinel lithium manganese oxide core have a polyhedral morphology.

[0067] In some embodiments of this application, the average particle size D50 of the primary particles of the doped spinel lithium manganese oxide core is 50 nm to 500 nm.

[0068] The positive effects of controlling the average primary particle size D50 of doped spinel lithium manganese oxide cores: If the average primary particle size D50 of the core is below 50 nm, the particle size is too small, leading to an excessively large specific surface area, resulting in interfacial side reactions, manganese dissolution, increased surface defects, and difficulty in forming a continuous and dense coating layer. If the average primary particle size D50 of the core is above 500 nm, the distance for lithium ions to diffuse from the particle surface to the internal active sites is long, resulting in a slow insertion / extraction rate and rapid capacity decay. Therefore, the average primary particle size D50 of the core is controlled within the range of 50 nm to 500 nm.

[0069] In some embodiments of this application, the primary particles of the doped spinel lithium manganese oxide core are pure-phase spinel structures with space group Fd-3m.

[0070] The pure-phase spinel structure with Fd-3m space group ensures that the core is free of impurities, avoiding side reactions and capacity loss; its three-dimensional tunnel structure provides a fast diffusion channel for lithium ions, ensuring high-rate performance and structural stability.

[0071] In some embodiments of this application, the primary particles of the doped spinel lithium manganese oxide core have an octahedral or truncated octahedral morphology.

[0072] In some embodiments of this application, the average particle size D50 of the primary particles of the doped spinel lithium manganese oxide core is 150 nm to 300 nm.

[0073] The positive effects of the primary average particle size D50 of the preferred spinel lithium manganese oxide core: The primary average particle size range of this preferred core can control the lithium ion solid-phase diffusion path within an extremely short range, ensuring rapid insertion and extraction at high rates, and can also make the specific surface area moderate, effectively suppressing interfacial side reactions and manganese dissolution, ensuring high-temperature cycling stability.

[0074] In some embodiments of this application, in the XRD pattern of the primary particles of the doped spinel lithium manganese oxide core, the ratio of the diffraction peak intensity of the (111) crystal plane to the diffraction peak intensity of the (400) crystal plane is in the range of 2.4≤I(111) / I(400)≤2.6.

[0075] In this application, I(111) and I(400) represent the diffraction peak intensities of spinel lithium manganese oxide (LiMn2O4) on the corresponding crystal planes (111) and (400) in the X-ray diffraction (XRD) pattern, respectively. The ratio I(111) / I(400) is used to quantify the degree of preferred orientation of the crystal plane of the material. In this application, the degree of preferred orientation (OI) of spinel lithium manganese oxide is defined as: OI=I(111) / I(400). The ratio of the diffraction peak intensity of the (111) crystal plane to that of the (400) crystal plane is within the range of 2.4≤I(111) / I(400)≤2.6. Doping treatment promotes the preferred orientation of the material on the (111) crystal plane, which is beneficial to reducing the manganese ion (Mn) content. 3+ / Mn 4+ The dissolution rate of Mn is reduced, thereby inhibiting the dissolution of Mn and improving the cycling stability and electrochemical performance of the material.

[0076] On the other hand, this application provides a method for preparing a spinel lithium manganese oxide cathode material, comprising the following steps: S1: Containing Mn 2+ A co-precipitation reaction is carried out by adding a soluble salt solution of the doped cation, a precipitant solution, and a complexing agent in a parallel flow to obtain the doped precursor; S2: The doped precursor and lithium source are uniformly mixed at a molar ratio (Mn+M):Li of 1:0.48~0.58, and sintered in an oxygen-containing atmosphere to obtain a doped spinel lithium manganese oxide core. S3: The spinel lithium manganese oxide core is mechanically mixed with manganese hydroxide to obtain manganese hydroxide-coated lithium manganese oxide. The manganese hydroxide-coated lithium manganese oxide is mixed with a lithium source, wherein the molar ratio of manganese atoms in the manganese hydroxide to lithium atoms in the lithium source (Mn:Li) is 2:1. The mixture is then sintered at high temperature in an oxygen-containing atmosphere to obtain the spinel lithium manganese oxide cathode material.

[0077] Mn was obtained in the liquid phase by co-precipitation. 2+ Uniform mixing with doped cations ensures that the dopant element uniformly substitutes for Mn sites in the crystal lattice. A high-temperature solid-state reaction yields a stable, regularly morphologically regular, and uniformly sized doped spinel lithium manganese oxide core. Mechanical fusion achieves uniform coating with manganese hydroxide. During high-temperature lithiation, the manganese hydroxide coating grows outward from the core surface, forming an epitaxial growth interface. This allows the manganese hydroxide coating to be transformed in situ into a near-monocrystalline lithium manganese oxide coating, with a continuous lattice and no obvious phase boundary at the interface, enabling smooth lithium ion transport across the interface. The preparation method is simple, cost-controllable, and suitable for industrial production.

[0078] In some embodiments of this application, in step S1, a soluble salt solution is prepared according to the chemical formula of the doped spinel lithium manganese oxide core, where the molar ratio of Mn:M is (2-x):x, and 0 < x ≤ 0.5. By precisely controlling the molar ratio of Mn to M, the co-precipitation method was used to achieve uniform mixing and distribution of dopants in the spinel lithium manganese oxide core, creating a lattice-matched and smooth substrate for the subsequent epitaxial growth of a quasi-monocrystalline lithium manganese oxide coating layer.

[0079] In the example, the soluble salts doped with cations can be aluminum sulfate, aluminum nitrate, aluminum chloride, magnesium sulfate, magnesium nitrate, magnesium chloride, titanium sulfate, titanium tetrachloride, zirconium nitrate, zirconium sulfate, zirconium chloride, niobium oxalate, niobium chloride, tantalum chloride, gallium nitrate, gallium chloride, sodium borate, strontium nitrate, strontium chloride, barium nitrate, barium chloride, lanthanum nitrate, lanthanum chloride, cerium nitrate, cerium chloride, etc.

[0080] In some embodiments of this application, the precipitant in step S1 is selected from one or more of sodium hydroxide and potassium hydroxide.

[0081] In some embodiments of this application, the complexing agent in step S1 is selected from one or more of ammonia, ammonium carbonate, and ammonium bicarbonate.

[0082] In some embodiments of this application, the flow rate of the soluble salt solution containing the doped cation is reduced in stages during step S1, and the flow rate is 20 mL / min to 5 mL / min.

[0083] In some embodiments of this application, the temperature of the co-precipitation reaction in step S1 is 40°C to 80°C.

[0084] In some embodiments of this application, the pH value of the co-precipitation reaction in step S1 is 9.0 to 13.0.

[0085] In some embodiments of this application, oxygen is introduced for pre-oxidation during the co-precipitation reaction in step S1, with an oxygen flow rate of 1 m³ / s. 3 / h~10m 3 / h.

[0086] During the coprecipitation reaction, manganese tetroxide precursor is generated by introducing oxygen. The distribution of dopant elements in the precursor is controlled by adjusting the flow rate of the soluble salt solution of the doped cation, the flow rate of oxygen, and the pH value, so that the concentration of dopant elements decreases from the inside to the outside.

[0087] In some embodiments of this application, after the co-precipitation reaction in step S1 is completed, the co-precipitated slurry is further filtered, washed, and dried.

[0088] In some embodiments of this application, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium nitrate, lithium sulfate, lithium acetate, lithium phosphate, lithium fluoride, lithium chloride, and lithium citrate.

[0089] In some embodiments of this application, the oxygen-containing atmosphere is air or oxygen, and the gas flow rate is 1 m / s². 3 / h~10m 3 / h.

[0090] In some embodiments of this application, the sintering process further includes crushing and sieving, with a sieving mesh size of 200 to 500 mesh.

[0091] In some embodiments of this application, the sintering temperature in step S2 is 700℃~900℃.

[0092] The positive effects of controlling the sintering temperature in step S2 to be between 700℃ and 900℃ are as follows: When the sintering temperature is below 700℃, grain growth is insufficient, resulting in small and irregular grains with excessively large specific surface areas, exacerbating side reactions; when the sintering temperature is above 900℃, grain growth is excessive, the lithium-ion diffusion path becomes longer, rate performance decreases, and particles are prone to agglomeration, affecting dispersibility and compaction density. Therefore, the sintering temperature in step S2 is controlled to be between 700℃ and 900℃.

[0093] In some embodiments of this application, the sintering time in step S2 is 8h to 24h.

[0094] The positive effects of controlling the sintering time in step S2 to be 8h–24h are as follows: Sintering time less than 8h results in incomplete reaction, residual impurities, low crystallinity, irregular particle morphology, and insufficient gradient doping, leading to low material capacity and poor cycle stability. Sintering time greater than 24h leads to excessive grain growth, longer lithium-ion diffusion paths, decreased rate performance, more uniform dopant distribution, and disruption of the gradient structure. Therefore, the sintering time in step S2 should be controlled to be 8h–24h.

[0095] In some embodiments of this application, step S3 further includes premixing and sieving before mechanical mixing, with a sieving mesh size of 200 to 500 mesh.

[0096] Premixing and screening ensures that the doped spinel lithium manganese oxide core and battery-grade micron-sized manganese hydroxide are initially and evenly dispersed, removing agglomerates and large particle impurities, and providing a uniformly mixed material for subsequent mechanical fusion processes.

[0097] In some embodiments of this application, the manganese hydroxide in step S3 is battery-grade micron-sized manganese hydroxide.

[0098] In some embodiments of this application, the mechanical mixing in step S3 is a combination of low-speed mixing and high-speed mixing performed sequentially, with the low-speed mixing speed being 500 rpm to 2000 rpm and the high-speed mixing speed being 3000 rpm to 6000 rpm.

[0099] The mechanical mixing process utilizes the centrifugal force, friction, and impact generated by high-speed rotation to induce intense collisions, friction, and fusion between the coating material and the core, thereby achieving uniform coating of manganese hydroxide onto the surface of the spinel lithium manganese oxide core. Low-speed mixing ensures initial homogenization of battery-grade micron-sized manganese hydroxide with the core, preventing localized agglomeration and avoiding core breakage due to excessive initial impact. High-speed mixing utilizes high shear force to plastically deform the manganese hydroxide particles, tightly adhering them to the core surface to form a continuous, dense, and uniform manganese hydroxide-coated lithium manganese oxide. This mechanical mixing coating process offers advantages such as simple preparation, high controllability, low production cost, suitability for large-scale mass production, and the ability to establish a good interfacial bond between the coating layer and the core.

[0100] In some embodiments of this application, the mechanical mixing time in step S3 is 1 min to 10 min.

[0101] The positive effects of controlling the mechanical mixing time in step S3 to be between 1 min and 10 min are as follows: When the mechanical mixing time is less than 1 min, manganese hydroxide cannot be fully coated, resulting in a discontinuous and uneven coating layer, exposed defects on the core surface, and low compaction density; when the mechanical mixing time is greater than 10 min, the core particles are easily broken, the surface lattice is easily damaged, introducing more defects, and manganese hydroxide may locally detach or agglomerate, which is not conducive to the formation of a uniform and dense shell. Therefore, the mechanical mixing time in step S3 should be controlled to be between 1 min and 10 min.

[0102] In some embodiments of this application, the sintering temperature in step S3 is 700℃~900℃.

[0103] The positive effects of controlling the sintering temperature in step S3 to be 700℃~900℃ are as follows: When the sintering temperature is below 700℃, the solid-phase reaction is insufficient, the precursor cannot be completely transformed into a spinel structure, and the product contains residual impurities such as Mn2O3. The shell is loose and not dense, and cannot form chemical bonds with the core. The interface impedance is high, the coating layer has poor protection effect, manganese dissolution is serious, and the high-temperature cycling performance and rate performance are significantly reduced. When the sintering temperature is above 900℃, the grains grow excessively, the lithium-ion diffusion path becomes longer, the rate performance deteriorates, the core gradient doping distribution is destroyed, the surface doping concentration increases, which hinders lithium-ion insertion and extraction, lithium volatilization is aggravated, and lithium-deficient impurities are easily generated, leading to the overall deterioration of the material performance.

[0104] In some embodiments of this application, the sintering time in step S3 is 8h to 24h.

[0105] The positive effects of controlling the sintering time in step S3 to be 8h–24h are as follows: When the sintering time is less than 8h, the transformation is incomplete, unreacted impurities remain in the coating layer, grain fusion is insufficient, and the core cannot be effectively protected, resulting in poor high-temperature cycling performance and low compaction density. When the sintering time is greater than 24h, excessive grain growth occurs, the coating layer thickness increases, cracks are easily generated, and the gradient doping structure of the core is destroyed, leading to a decrease in the rate performance and capacity of the material. Therefore, the sintering time in step S3 should be controlled to be 8h–24h.

[0106] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on weight, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0107] Example 1 Step S1: Preparation of gradient-doped precursor Configure Mn respectively 2+ The concentration was 1.94 mol / L, Al 3+ The concentration is 0.04 mol / L, Mg 2+ A 0.02 mol / L solution of soluble salts of MnSO4, Al2(SO4)3, and MgSO4 was kept at a constant temperature of 60°C in a continuously stirred reactor, with oxygen continuously introduced at a flow rate of 5 m / s. 3 / h, a soluble salt solution, ammonia water, and sodium hydroxide solution are added to the reactor in parallel flow using a constant flow pump, and the Al in the constant flow pump is... 3+ Mg 2+ The soluble salt solution was added at four different flow rates: 20 mL / min, 15 mL / min, 10 mL / min, and 5 mL / min, for a total time of 12 h. The pH was maintained at 10.5 using ammonia and sodium hydroxide solution. After the reaction was complete, the precipitate was filtered, washed, and dried to obtain a manganese tetroxide precursor with Al and Mg gradient doping.

[0108] Step S2: Lithification sintering Al and Mg graded-doped manganese tetroxide precursors were mixed with Li₂CO₃ at a molar ratio (Mn+Al+Mg:Li) of 1:0.54 at a high-speed mixing speed of 600 rpm. The mixture was placed in a muffle furnace under an air atmosphere with a gas flow rate of 5 m / s.3 The temperature was increased to 800℃ at a rate of 3℃ / min and sintered at that temperature for 15 hours. After natural cooling, the material was crushed and sieved through a 200-mesh sieve to obtain Al and Mg graded doped spinel lithium manganese oxide core material. TEM analysis showed that the primary particles were regular octahedrons with an average particle size of 200 nm.

[0109] Step S3: Construct a surface-like monocrystalline lithium manganese oxide coating layer 300g of the above-mentioned spinel lithium manganese oxide core material was mixed with battery-grade micron-sized manganese hydroxide and then sieved through a 200-mesh sieve. The mixed powder material was fed into a high-efficiency vibratory fusion coating machine and mixed at 1000 rpm for 2 min, followed by mixing at 5000 rpm for 10 min. The powder material was then removed and dried to obtain lithium manganese oxide material coated with manganese hydroxide. The lithium manganese oxide coated with manganese hydroxide was mixed with Li₂CO₃, wherein the molar ratio of manganese atoms in the manganese hydroxide to lithium atoms in the lithium source was 2:1. The mixture was placed in an air-filled muffle furnace with a gas flow rate of 5 m / s. 3 The temperature was increased to 800℃ at a rate of 3℃ / min, held for 8 hours, crushed, and passed through a 200-mesh sieve to obtain spinel lithium manganese oxide (chemical formula Li) with an Al and Mg gradient doped core. 1.08 Mn 1.94 Al 0.04 Mg 0.02 O4), with a shell of quasi-monocrystalline lithium manganese oxide composite cathode material, the resulting cathode material can be represented by the chemical formula Li. 1.08 Mn 1.94 Al 0.04 Mg 0.02 O4@LiMn2O4 has an average particle size D50 of 11 μm and a coating layer Mn loading of approximately 1 wt%.

[0110] Figure 1 This is a TEM image of the spinel lithium manganese oxide cathode material prepared in Example 1.

[0111] Example 2 The difference between this embodiment and Embodiment 1 is that in step S1, Al2(SO4)3 is used instead of MgSO4+Al2(SO4)3 for gradient doping, and Mn is prepared accordingly. 2+ The concentration was 1.94 mol / L, Al 3+ A 0.06 mol / L solution of soluble salts of MnSO4 and Al2(SO4)3 was used to pump Al from a constant flow pump. 3+The soluble salt solution was added at four different flow rates: 20 mL / min, 15 mL / min, 10 mL / min, and 5 mL / min, for 12 hours. In step S2, the Al-doped manganese tetroxide precursor and Li₂CO₃ were mixed at high speed in a molar ratio (Mn+Al):Li of 1:0.54. The remaining steps and parameters were identical to those in Example 1. This yielded spinel lithium manganese oxide (chemical formula Li₂CO₃) with an Al-doped core. 1.08 Mn 1.94 Al 0.06 O4), a composite cathode material with a pure, single-crystal lithium manganese oxide coating layer, the resulting cathode material can be represented by the chemical formula Li. 1.08 Mn 1.94 Al 0.06 O4@LiMn2O4 has an average particle size D50 of 10 μm and a coating layer Mn loading of 1 wt%.

[0112] Example 3 The difference between this embodiment and Embodiment 1 is that in step S1, MgSO4 is used instead of MgSO4+Al2(SO4)3 for gradient doping, and Mn is prepared accordingly. 2+ The concentration was 1.94 mol / L, Mg 2+ A 0.06 mol / L solution of soluble salts of MnSO4 and MgSO4 was used to pump MgSO4 from a constant flow pump. 2+ The soluble salt solution was added at four gradient flow rates: 20 mL / min, 15 mL / min, 10 mL / min, and 5 mL / min, for 12 h. In step S2, the Mg-doped manganese tetroxide precursor was mixed with Li₂CO₃ at a molar ratio (Mn+Mg):Li of 1:0.54 at high speed. The remaining steps and parameters were exactly the same as in Example 1. This yielded a spinel lithium manganese oxide (chemical formula Li₂CO₃) with a Mg-doped core. 1.08 Mn 1.94 Mg 0.06 O4), with a shell of quasi-monocrystalline lithium manganese oxide composite cathode material, the resulting cathode material can be represented by the chemical formula Li. 1.08 Mn 1.94 Mg 0.06 O4@LiMn2O4 has an average particle size D50 of 10 μm and a coating layer Mn loading of 1 wt%.

[0113] Comparative Example 1 Configure Mn 2+A 2 mol / L MnSO4 solution was kept at a constant temperature of 60 °C in a continuously stirred reactor. The MnSO4 solution, ammonia, and sodium hydroxide solution were added to the reactor in a co-current flow rate of 10 mL / min over 12 h using a constant flow pump. The pH was maintained at 10.5 using ammonia and sodium hydroxide solutions. After the reaction was complete, the precipitate was filtered, washed, and dried to obtain the manganese hydroxide precursor.

[0114] Manganese hydroxide precursor and Li₂CO₃ were mixed at a high speed of 600 rpm at a molar ratio of Mn:Li of 1:0.54. The mixture was placed in a muffle furnace under an air atmosphere with a gas flow rate of 5 m / s. 3 The temperature was increased to 800℃ at a rate of 3℃ / min and sintered at that temperature for 8 hours. After natural cooling, the material was crushed and sieved through a 200-mesh sieve to obtain undoped and uncoated spinel lithium manganese oxide cathode material. The chemical formula of the obtained cathode material can be represented as LiMn2O4, and its average particle size D50 is 10μm.

[0115] Comparative Example 2 Configure Mn respectively 2+ The concentration was 1.94 mol / L, Al 3+ A 0.06 mol / L solution of soluble salts of MnSO4 and Al2(SO4)3 was maintained at a constant temperature of 60°C in a continuously stirred reactor. The soluble salt solution, ammonia, and sodium hydroxide solution were fed into the reactor concurrently via a constant flow pump. The Al2(SO4)3 solution was then pumped into the reactor. 3+ The soluble salt solution was added at four different flow rates: 20 mL / min, 15 mL / min, 10 mL / min, and 5 mL / min, for a total time of 12 h. The pH was maintained at 10.5 using ammonia and sodium hydroxide solution. After the reaction was complete, the precipitate was filtered, washed, and dried to obtain an Al-doped manganese tetroxide precursor.

[0116] Al-doped manganese tetroxide precursor was mixed with Li₂CO₃ at a molar ratio (Mn+Al):Li of 1:0.54 at a high-speed mixing rate of 600 rpm. The mixture was placed in a muffle furnace under an air atmosphere with a gas flow rate of 5 m / s. 3 The temperature was increased to 800℃ at a rate of 3℃ / min and sintered at that temperature for 8 hours. After natural cooling, the material was crushed and sieved through a 200-mesh sieve to obtain Al-gradient-doped spinel lithium manganese oxide cathode material. The chemical formula of the obtained cathode material can be represented as Li 1.1 Mn 1.94 Al 0.06 O4 has an average particle size D50 of 10 μm and a coating layer with a Mn loading of approximately 1 wt%.

[0117] Comparative Example 3 Configure Mn respectively 2+ The concentration was 1.94 mol / L, Mg 2+ A 0.06 mol / L solution of soluble MnSO4 and MgSO4 was maintained at a constant temperature of 60°C in a continuously stirred reactor. The soluble salt solution, ammonia, and sodium hydroxide solution were fed into the reactor concurrently via a constant flow pump. The MgSO4 solution was then pumped into the reactor. 2+ The soluble salt solution was added at four different flow rates: 20 mL / min, 15 mL / min, 10 mL / min, and 5 mL / min, over a period of 12 h. The pH was maintained at 10.5 using ammonia and sodium hydroxide solution. After the reaction was complete, the precipitate was filtered, washed, and dried to obtain a Mg-doped manganese tetroxide precursor.

[0118] A Mg-doped manganese tetroxide precursor was mixed with Li₂CO₃ at a molar ratio (Mn+Mg):Li of 1:0.54 at a high-speed mixing rate of 600 rpm. The mixture was placed in a muffle furnace under an air atmosphere with a gas flow rate of 5 m³ / min. 3 The temperature was increased to 800℃ at a rate of 3℃ / min and sintered at that temperature for 8 hours. After natural cooling, the material was crushed and sieved through a 200-mesh sieve to obtain Mg-gradient-doped spinel lithium manganese oxide cathode material. The chemical formula of the obtained cathode material can be represented as Li 1.1 Mn 1.94 Mg 0.06 O4 has an average particle size D50 of 10 μm and a coating layer with a Mn loading of approximately 1 wt%.

[0119] Figure 2 The images show the XRD patterns of the spinel lithium manganese oxide cathode materials prepared in Examples 1-3 and Comparative Examples 1-3.

[0120] Figure 3 Comparison of XRD diffraction peaks of the (111) crystal plane of the spinel lithium manganese oxide cathode materials prepared in Examples 1-3 and Comparative Examples 1-3.

[0121] The (111) crystal plane is the most densely packed atomic plane in lithium manganese oxide crystals, exhibiting low surface energy and high structural stability. Studies have shown that lithium manganese oxide materials with exposed (111) crystal planes exhibit high manganese ion (Mn) concentration during electrochemical cycling or high-temperature storage. 3+ / Mn 4+ The low dissolution rate of Mn effectively inhibits its dissolution, thereby improving the cycling stability and electrochemical performance of the material. Figure 3The results show that the doped materials of Examples 1-3 and Comparative Examples 2 and 3 have an improved I(111) / I(400) compared to the undoped lithium manganese oxide material of Comparative Example 1. This indicates that the doping treatment promotes the preferred orientation of the material on the (111) crystal plane. This preferred orientation helps to enhance the strength of the particles and the stability of the crystal structure, laying the foundation for further improving the cycling performance of the material.

[0122] Table 1 shows the comparison of I(111) / I(400) of spinel lithium manganese oxide cathode materials.

[0123] Table 1 Comparison of I(111) / I(400) of spinel lithium manganese oxide cathode materials

[0124] The performance of the prepared spinel lithium manganese oxide cathode material was tested.

[0125] The lithium manganese oxide cathode materials obtained in the examples and comparative examples were assembled into CR2032 coin cells for electrochemical performance testing. A lithium metal sheet was used as the negative electrode, and a Celgard 2400 polypropylene microporous membrane was used as the separator. The electrolyte was 1 mol / L LiPF6 (EC:DEC = 1:1, v / v). The cathode, negative electrode, separator, and electrolyte were assembled in an argon glove box with a water and oxygen content of less than 1 ppm. After assembly, the cells were allowed to stand for 24 hours to obtain the battery. The discharge specific capacity (mAh / g) at different rates (0.2C, 1C) and the capacity retention at 1C were tested in a constant temperature chamber at 55°C under charge / discharge cutoff voltages of 3.0V to 4.3V. The tap density of the materials was also tested (g / cm³). 3 ) and compaction density (g / cm 3 ).

[0126] The evaluation results of each performance item are shown in Table 2.

[0127] Table 2 Performance test results of spinel lithium manganese oxide cathode material

[0128] The performance test results of the embodiments and comparative examples show that Embodiments 1-3 all exhibit excellent high-temperature cycling stability and high tap density and compaction density, which proves the effectiveness of the technical solution of the present invention and a certain parameter tolerance.

[0129] Comparative Example 1 exhibits the worst high-temperature cycling performance, tap density, and compaction density due to the intrinsic characteristics of lithium manganese oxide.

[0130] Compared with Examples 1-3, Comparative Example 2 has poor high-temperature cycling performance due to the lack of interface protection from the coating layer, and its tapped density and compacted density are also lower.

[0131] Compared with Examples 1-3, Comparative Example 3 has poor high-temperature cycling performance due to the lack of interface protection from the coating layer, and its tapped density and compacted density are also lower.

[0132] Comparative Examples 2 and 3 also demonstrate that the quasi-monocrystalline lithium manganese oxide coating is indispensable for improving the high-temperature cycling performance, tap density, and compaction density of the material.

[0133] The above embodiments and data fully demonstrate that, through the synergistic design of "doped spinel lithium manganese oxide core" and "homogeneous electrochemically active single-crystal lithium manganese oxide coating layer", the present invention has for the first time achieved a simultaneous balance of high-temperature cycling stability, high tap density and compaction density, and excellent rate performance in spinel lithium manganese oxide cathode materials, achieving significant beneficial effects.

[0134] It should be noted that there is a trade-off between the capacity and structural stability of spinel lithium manganese oxide cathode materials. This invention, through synergistic modification via doping and coating, although resulting in a slight decrease in initial specific capacity compared to unmodified materials, significantly improves high-temperature cycling stability, tap density, and compaction density, demonstrating overall performance significantly superior to existing technologies. Those skilled in the art will understand that this technical solution, which trades off a substantial increase in stability and energy density within an acceptable capacity loss range, has significant practical value in the field of lithium-ion batteries.

[0135] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A spinel lithium manganese oxide cathode material, characterized in that, The spinel lithium manganese oxide cathode material includes a doped spinel lithium manganese oxide core and a near-monocrystalline lithium manganese oxide coating layer covering the doped spinel lithium manganese oxide core. The chemical formula of the doped spinel lithium manganese oxide core is Li a Mn 2-x M x O4, where 0.95≤a≤1.10, 0<x≤0.5, and M is a doping element selected from one or more of B, Mg, Al, Ti, Ga, Sr, Zr, Nb, Ba, La, Ce, and Ta; The doped spinel lithium manganese oxide core is a gradient-doped spinel lithium manganese oxide, with the doping concentration decreasing from the inside to the outside. The preparation method of the spinel lithium manganese oxide cathode material includes the following steps: S1: Containing Mn 2+ A co-precipitation reaction is carried out by adding a soluble salt solution of the doped cation, a precipitant solution, and a complexing agent in a co-flow manner to obtain the doped precursor; S2: The doped precursor and lithium source are uniformly mixed according to the molar ratio, and sintered in an oxygen-containing atmosphere to obtain a doped spinel lithium manganese oxide core. S3: The spinel lithium manganese oxide core is mechanically mixed with manganese hydroxide to obtain manganese hydroxide-coated lithium manganese oxide. The manganese hydroxide-coated lithium manganese oxide is mixed with a lithium source, wherein the molar ratio of manganese atoms in the manganese hydroxide to lithium atoms in the lithium source (Mn:Li) is 2:

1. The mixture is then sintered at high temperature in an oxygen-containing atmosphere to obtain the spinel lithium manganese oxide cathode material. The sintering temperature in step S2 is 700℃~800℃; The sintering time in step S2 is 8h to 15h; In step S3, the mechanical mixing is performed sequentially as low-speed mixing and high-speed mixing, with low-speed mixing at 500 rpm to 2000 rpm and high-speed mixing at 3000 rpm to 6000 rpm. The sintering temperature in step S3 is 700℃~900℃; The sintering time in step S3 is 8h to 24h.

2. The spinel lithium manganese oxide cathode material according to claim 1, characterized in that, The mass of the monocrystalline lithium manganese oxide coating layer accounts for 0.2% to 5.0% of the total mass of the spinel lithium manganese oxide cathode material.

3. The spinel lithium manganese oxide cathode material according to claim 1, characterized in that, The doping element is Al and / or Mg; And / or, the primary particles of the doped spinel lithium manganese oxide core have a polyhedral morphology; And / or, the average particle size D50 of the primary particles of the doped spinel lithium manganese oxide core is 50 nm to 500 nm; And / or, the primary particles of the doped spinel lithium manganese oxide core are pure-phase spinel structures with space group Fd-3m.

4. The spinel lithium manganese oxide cathode material according to claim 3, characterized in that, The primary particles of the doped spinel lithium manganese oxide core have an octahedral or truncated octahedral morphology. And / or, the average particle size D50 of the primary particles of the doped spinel lithium manganese oxide core is 150 nm to 300 nm.

5. The spinel lithium manganese oxide cathode material according to claim 1, characterized in that, In the primary particle XRD pattern of the doped spinel lithium manganese oxide core, the ratio of the diffraction peak intensity of the (111) crystal plane to that of the (400) crystal plane is in the range of 2.4≤I(111) / I(400)≤2.

6.

6. The spinel lithium manganese oxide cathode material according to claim 1, characterized in that, In step S1, a soluble salt solution is prepared according to the chemical formula of the doped spinel lithium manganese oxide core, in which the molar ratio of Mn:M is (2-x):x, where 0 < x ≤ 0.

5. And / or, in step S1, the precipitant is selected from one or more of sodium hydroxide and potassium hydroxide; And / or, in step S1, the complexing agent is selected from one or more of ammonia, ammonium carbonate, and ammonium bicarbonate; And / or, in step S1, the flow rate of the soluble salt solution of the doped cation is reduced in stages, wherein the flow rate is 20 mL / min to 5 mL / min; And / or, the temperature of the co-precipitation reaction in step S1 is 40℃~80℃; And / or, the pH value of the co-precipitation reaction in step S1 is 9.0 to 13.0; And / or, in step S1, oxygen is introduced for pre-oxidation during the co-precipitation reaction, with an oxygen flow rate of 1 m³ / s. 3 / h~10m 3 / h; And / or, after the co-precipitation reaction in step S1 is completed, the co-precipitated slurry is further filtered, washed and dried.

7. The spinel lithium manganese oxide cathode material according to claim 1, characterized in that, The lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium oxide, lithium oxalate, lithium nitrate, lithium sulfate, lithium acetate, lithium phosphate, lithium fluoride, lithium chloride, and lithium citrate. And / or, the oxygen-containing atmosphere is air or oxygen, and the gas flow rate is 1 m / s². 3 / h~10m 3 / h; And / or, the sintering process further includes crushing and sieving, with a sieving mesh size of 200 to 500 mesh.

8. The spinel lithium manganese oxide cathode material according to claim 1, characterized in that, In step S3, the manganese hydroxide is battery-grade micron-sized manganese hydroxide. And / or, in step S3, premixing and screening are further performed before mechanical mixing, with a screening mesh size of 200 mesh to 500 mesh; And / or, the mechanical mixing time in step S3 is 1 min to 10 min.

Citation Information

Patent Citations

  • Power spinel lithium manganese oxide anode material and preparation method thereof

    CN101807682A

  • Lithium battery cathode material and preparation method thereof as well as lithium battery

    CN105680025A

  • Core-shell isomerous lithium ion battery composite positive electrode material formed by layered lithium-rich manganese base and spinel type lithium manganate and preparation method of positive electrode material

    CN107086298A

  • Composite lithium manganate, preparation method thereof, positive electrode, battery and electric device

    CN118676324A

  • Manganese-based composite positive electrode material and preparation method and application thereof

    CN119833606A